(untitled) (Journal of the College of Basic Education, 2024)
The narrations of Al-Hafiz Ahmed bin Sinan bin Asad bin Haban in the six books_ an analytical study_ it became clear from the study of his life that he is one of the imams of hadith, the trustworthy memorizers, and he was the imam of the people of his time. Aaron, I studied his narrations (35) A hadith in the six books, and that is by extracting it from its original sources, then studying the men of attribution, then judging the attribution of the hadith after examining the words of the scholars of al-Jarh and at-Ta’deel, showing after that what is in the hadiths of strange hadiths and the meanings of vocabulary from books of strange hadiths and dictionaries of the language, then explaining the hadiths In general, from the books of explanations, then he mentioned the benefits deduced from the hadith, and the research plan was as follows: The research plan was as follows: The first topic: Fadila Talha: In it: The first requirement: GraduationThe second requirement: studying the chain of transmission, the third requirement: judging the hadith, and the fourth requirement: the overall meaning of the hadith.